Development of nutrition label use scale for patients of coronary heart disease and examination of its reliability and validity - Pan, Lu; Xie, Caixia; Liu, Mengjiao (Frontiers in Psychology, 2023)
Background: A proper evaluation on the intention of using nutrition label in patients with coronary heart disease (CHD) is crucial to design and formulate of behavior-based interventions. A valid and reliable instrument based on theoretical basis is needed to measure individual intention towards nutrition label use and identify underlying socio-cognitive factors.Object: To develop and test validity and reliability of the theoretically based nutrition label use (NLU) scale and to promote the use of nutrition labels in CHD patients.A questionnaire was developed based on the theory of planned behavior (TPB), empirical literatures, expert review and pilot tested. A total of 460 CHD patients in a hospital in Changsha were investigated using this questionnaire from April 2021 to August 2021. The items and dimensions in the scale were explored and confirmed using item-analysis, content validity, exploratory factor analytical (EFA), confirmatory factor analytical (CFA), internal consistency and split-half reliability tests.Results: A total of 33 items with 4 structural factors were identified, including 10 items of attitude, 6 items of subjective norm, 12 items of perceived behavior control, and 5 items of intention. The total variance explained by the EFA model was 68.563%. The model was further tested with CFA. The measurement model fitted the data well (Ratio of chi-square minimum and degree of freedom (CMIN/DF) =1.743, goodness of fit index (GFI) =0.814, incremental fit index (IFI) =0.946, Tuker-Lewis index (TLI) =0.940, the comparative fit index (CFI) =0.945, the root mean square error of approximation (RMSEA) =0.057). The content validation index (CVI) of the scale was 0.82, and the CVI of the items ranged from 0.8 to 1.00. The reliability of the scale was 0.976 (p<0 .001) using Cronbach's alpha and 0.937 (p < 0.001) using the split-half coefficient.The newly developed Nutrition Label Use Scale can serve as a valid and reliable tool to evaluate the nutrition label use of CHD patients.